Early Divorce Causes and Manifestations : A Field – Study in Al – Sharjah - عبد الله معروف, آلاء (Al-Adab Journal, 2018)
The objectives of current study were identify the causes of early divorce from women view and men view divorced, to achieve these objectives, divorce questionnaire contained (29) items was structured women and men view point, depending on the social exchange theory, reliability and validity were consisted. The participants of current study were (60) individuals (30) men divorced and (30) women divorced. The results of current study were, a major cause of early divorce from men divorced view point was control of the luxuries. And for women divorced view point was the suspicious ties for men in the social network. the study ended with some recommendations and future studies.